FACHSPRACHSPEZIFISCHER WORTSCHATZ ALS INSTRUMENT ZUR MARKENPFLEGE AM BEISPIEL DER KATEGORIE ELEKTROMOBILITÄT IM VOLKSWAGEN MAGAZIN - Błaszkowska, Hanka (Neofilolog, 2018)
The article explores the influence of the specialised language on the shaping of the image of the German car brand Volkswagen. The analysed material comprises marketing texts from an image magazine of the Volkswagen Magazin brand, available on the company’s website. The issue will be examined on the basis of the semantic category of Electro Mobility, which constitutes a subcategory of the semantic category of innovation, which in turn is currently the company’s main area of activity and the focus of all actions, also linguistic, in terms of shaping the brand’s image. The specialised language in the texts from the Magazine, a digital journal, whose articles resemble forms of journalistic writing, limits itself mainly to specialist vocabulary – the technical vocabulary referring to automotive technology, as well as pseudo-specialised language, whose role is merely to evoke technical connotations. Both types of specialist terminology contribute to the restoring of the reputation of the brand in the eyes of the consumers, which has been severely affected as a result of the emissions scandal in 2015.